Antibacterial and antioxidant activity of different solvent extractions of leaves and bark of Erythrina variegata - Thuvaragan, S.; Gnanakarunyan, T.; Bandaranayaka, T.D.; Horshington, A.S.; Fernando, K.M.O. (University of Jaffna, 2024)
Plant-based antimicrobials have been proven to be a promising treatment option with several advantages, including fewer side effects and highly diverse pharmacological activities due to secondary metabolites. Erythrina variegata, known as the Coral tree, possesses many therapeutic activities, including antibacterial, antioxidant, anthelminthic, anti-inflammatory, and cytotoxic activities, and is frequently used in Siddha medicine. Erythrina variegata is widely distributed in Malaysia, Sri Lanka, and India.
Keywords: Erythrina variegata; Antioxidant activity; Antibacterial activity